Les « grottes-sanctuaires » gallo-romaines du Morbihan, éléments d’une géographie du sacré chez les Vénètes - Patrick Galliou (La Bretagne Linguistique)
In Morbihan, three natural cavities, caves and rock shelters, explored briefly at the end of the 19th century and the beginning of the following century, yielded a wealth of archaeological material from the Roman period, mainly made up of white clay statuettes (Venus, mother goddesses, etc.). In all likelihood, these were places where underground divinities were worshipped in order to obtain abundant harvests. To date, there are no other known examples of such use of underground sites in the Roman period in the Armorican peninsula.